Heart rate recovery after the 6-min walk test in people with bronchiectasis - Juan Antonio Sáez-Pérez; Ane Arbillaga-Etxarri; Victoria Alcaraz-Serrano; Elena Gimeno-Santos; Antoni Torres; Beatriz Herrero-Cortina (ERJ Open Research)
Background The cardiac autonomic response to exercise and during recovery has been poorly explored in bronchiectasis. Methods A longitudinal study was conducted in adults with bronchiectasis. Sociodemographic and clinical data were collected at baseline and after 12 months of follow-up. The heart rate recovery after the first (HRR1) and second minute (HRR2) of recovery in the six-min walk test (6MWT) was estimated in both assessments. Adjusted regression models were used to identify predictors of a delayed HRR1 (HRR1≤14). Results 104 participants with a mean±sd age of 64±13 years and mostly women (67%) were included. A delayed HRR1 after the baseline 6MWT was identified in 36% of participants. These participants presented a higher proportion of males, increased body mass index, higher disease severity, more likely to require hospitalisation, more impact on quality of life, lower exercise capacity, lower heart rate at the end of the 6MWT and lower HRR2. Disease severity (β, 95% CI) (moderate and severe versus mild, −0.47 (−0.94 to −0.01)) and distance walked (0.34 (0.11 to 0.56)) were the independent variables associated with HRR1. Of the 45 participants who completed the entire follow-up period, 24% exhibited delayed HRR1. The presence of at least two exacerbations during the follow-up period (OR 16.89, 95% CI 1.44 to 197.48) was the only predictor of a delayed HRR1 in the assessment completed at the end of the study. Conclusion HRR1 is related to disease severity and is mainly affected by having severe exacerbations in people with bronchiectasis.